Social Networks and the Evolution of Leadership Theories in the Technical Environment - Cheng, Raymond; Tang, Wing Cheung (2017)
Historically, major over-investment bubbles and their subsequent crashes often bring about profound socioeconomic changes. Technological advancement and the style of leadership also played a similar role but in a different way. With the collaborative development of open-source Web service platforms (e.g. Apache) that are more stable, reliable (Boulanger, 2005) and more widely adopted than their proprietary competitors (e.g. Microsoft IIS), large-scale ‘server farms’ with much higher capacities have become possible (Tuomi, 2003). Leadership style in the hi-tech era, hence, also evolved to adopt to such changes, from Francis Galton’s (1892/2000) trait theory, Thomas Carlyle’s (1841) ‘Great Man’ theory, leader-member relations (Duchon, Green & Taber, 1986) and Burns’ (1978) transformational leadership to strategic leadership (Stumpf, 1988). Such evolution of leadership trend toward strategic leadership further favored the possibility of peer-to-peer technology (in which intense investment is generally required), and which, in turn, further expanded the scalability of the already rapidly growing computer networks (Nguyen, 2008) and fostered the adaptation of team work in the technical environment. This paper attempts to look at the evolution of social networks from the early 1980s to the present day along with the evolution of contemporary leadership theories applied within the technical environment over the last 20 years. Results showed that striking similarities exist between the evolution of leadership theories in the technical environment and the advancement of technology in the development of social networks – an invisible but clear link that is often overlooked by researchers.